2004
DOI: 10.1016/j.visres.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative properties of achromatic color induction: An edge integration analysis

Abstract: Edge integration refers to a hypothetical process by which the visual system combines information about the local contrast, or luminance ratios, at luminance borders within an image to compute a scale of relative reflectances for the regions between the borders. The results of three achromatic color matching experiments, in which a test and matching ring were surrounded by one or more rings of varying luminance, were analyzed in terms of three alternative quantitative edge integration models: (1) a generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 17 publications
8
85
0
Order By: Relevance
“…Yet, we find powerful edge responses that are almost identical for disk and surround modulations. Given the psychophysical evidence that edges play a key role in color and brightness perception (Reid and Shapley, 1988;Brenner and Cornelissen, 1991;Rudd and Arrington, 2001;Bindman and Chubb, 2004a,b;Hong and Shevell, 2004a,b;Rudd and Zemach, 2004;Shapiro et al, 2004), our results could be interpreted as evidence that surface filling-in is unnecessary and that edge responses alone, or in combination with local luminance, determine surface brightness (Blakeslee and McCourt, 1999;Dakin and Bex, 2003;Blakeslee and McCourt, 2004;Shapiro et al, 2004).…”
Section: Discussionmentioning
confidence: 56%
“…Yet, we find powerful edge responses that are almost identical for disk and surround modulations. Given the psychophysical evidence that edges play a key role in color and brightness perception (Reid and Shapley, 1988;Brenner and Cornelissen, 1991;Rudd and Arrington, 2001;Bindman and Chubb, 2004a,b;Hong and Shevell, 2004a,b;Rudd and Zemach, 2004;Shapiro et al, 2004), our results could be interpreted as evidence that surface filling-in is unnecessary and that edge responses alone, or in combination with local luminance, determine surface brightness (Blakeslee and McCourt, 1999;Dakin and Bex, 2003;Blakeslee and McCourt, 2004;Shapiro et al, 2004).…”
Section: Discussionmentioning
confidence: 56%
“…This implies that the illusory effects in the Grating Induction illusion are confined to the boundaries of the gray-strip [11,12]. From Figure 4a and 4b, it can be seen that the visibility threshold of the illusory effect increases with the wavelength of the background sine/ square wave.…”
Section: General Discussion and Inferencesmentioning
confidence: 87%
“…However perceived contrast of decremental gratings were not systematically studied previously under conditions similar to those reported here. Processing differences between positive and negative local contrast has been reported in literature both by behavioral and neuronal studies (e.g., Chubb & Nam, 2000;Rekauzke et al, 2016;Rudd & Zemach, 2004Sato et al, 2016;Whittle, 1986;Zaghloul et al, 2003). The light-dark asymmetry is also incorporated in some models of brightness (e.g., Rudd, 2013Rudd, , 2014.…”
Section: Discussionmentioning
confidence: 96%
“…4). Using rectified gratings allowed us to study positive and negative contrast patterns independently, which was critical because both behavioral and neural evidence in previous studies suggest fundamental differences between processing of incremental and decremental luminance patterns (e.g., Blackwell, 1946;Chubb & Nam, 2000;Economou, Zdravkovic, & Gilchrist, 2007;Kremkow, Jin, Wang, & Alonso, 2016;Patel & Jones, 1968;Rekauzke et al, 2016;Rudd & Zemach, 2004Sato, Motoyoshi, & Sato, 2016;Whittle, 1986;Zaghloul, Boahen, & Demb, 2003). Previous studies in literature have found interactions between spatial frequency and mean luminance in contrast perception using simple gratings (Chubb, Sperling, & Solomon, 1989;Georgeson & Sullivan, 1975;Peli et al, 1996;Robilotto & Zaidi, 2004;Van & Bouman, 1967).…”
Section: Introductionmentioning
confidence: 99%